Oxidation behaviour of the nickel-based superalloy DZ125 hot-dipped with Al coatings doped by Si. (November 2016) - Zang, Junjie; Song, Peng; Feng, Jing; Xiong, Xiping; Chen, Rong; Liu, Guangliang; Lu, Jiansheng
Highlights: Low cost and high efficiency hot-dipped Al-Si coating on DZ125 superalloy improve a better high-temperature anti-oxidation properties. Si in the outer layer of the coating sets a barrier to O as well as strongly segregating element (Hf, W, Ta) during high-temperature operation. The second phase SiCr3 in the inner layer of the Al-Si coating on DZ125 gathers W and Ta. Formation of the silicon-aluminium-based barrier layer due to different electronegativity of elements Si and Hf as well as Ta. Abstract: A pure Al coating and Al-Si coating were prepared on the surface of the DZ125 superalloy by hot-dipping. The Al-Si coating provides better thermal oxidation resistance than that of the pure Al coating due to the formation of a more compact Al2 O3 layer. The microstructure of the Al-Si coating shows a silicon-aluminium-based layer with Ta5 Si3 and AlHfSi phase forms after heat treatment in argon at 850 °C. This layer is a barrier to the diffusion of oxygen and other metal elements during cyclic oxidation, which has a significant effect on the formation of the compact Al2 O3 layer.